2021
DOI: 10.1002/aur.2541
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone versus aripiprazole fracture risk in children and adolescents with autism spectrum disorders

Abstract: Risperidone and aripiprazole, commonly used antipsychotics in children with autism spectrum disorder (ASD), have previously been associated with elevated fracture risk in other populations. The aim of this study was to evaluate and compare the risk of fracture among children with ASD using risperidone or aripiprazole. This was a retrospective, propensity‐score matched cohort study, set between January 2013 and December 2018. We used the MarketScan Medicaid insurance data, which covers multiple states of the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…12 Houghton et al found, in 2021, aripiprazole has a higher fracture prevalence in ASD children compared to risperidone. 13 A retrospective observational study between 2013 and 2018 includes 6624 children, aged 2 to 18 years, with ASD and on AP either risperidone or aripiprazole. 13 Fracture incidence was 23.2% with risperidone compared to 38.4% with aripiprazole.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…12 Houghton et al found, in 2021, aripiprazole has a higher fracture prevalence in ASD children compared to risperidone. 13 A retrospective observational study between 2013 and 2018 includes 6624 children, aged 2 to 18 years, with ASD and on AP either risperidone or aripiprazole. 13 Fracture incidence was 23.2% with risperidone compared to 38.4% with aripiprazole.…”
Section: Resultsmentioning
confidence: 99%
“…13 A retrospective observational study between 2013 and 2018 includes 6624 children, aged 2 to 18 years, with ASD and on AP either risperidone or aripiprazole. 13 Fracture incidence was 23.2% with risperidone compared to 38.4% with aripiprazole. 13…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations